Reduction of fish bycatch in shrimp trawl using a solid separator grid in the aft belly - Isaksen, Bjørnar; Valdemarsen, John Willy; Larsen, Roger B. (ICES, 1990)
During 1989-90 a new concept to avoid bycatch of fish in shrimp trawl has been developed in Norway. The system consists of an aluminium grid, 0.6 - 1.0 m wide and 1.3 - l.5 m long, with bars spaced 19 mm. The grid is installed in the extention piece in front of the codend, angled 45º, and with a fish outlet on the top. In front of the grid is mounted a guiding funnel or flapper. Several practical tests with commercial trawlers are conducted. Performance of the system and behaviour of fish and shrimp relative to it has been studied with a remote controlled underwater TV-vehicle. Escapement of fish like cod, haddock, redfish and Greenland halibut is better than with any bycatch device tested earlier. Handling cause no significant problems, neither on small nor larger shrimp trawlers. Loss of shrimp when using the system is acceptable, less than 5 %. An extensive effort is taking place to introduce this selective device in all Norwegian shrimp fisheries. From March 1. 1990 the separator grid was introduced by law in the northern coastal shrimp fishery.